NUTRITION AND EXERCISE HABITS AMONGST MEDICAL STUDENTS IN A PRIVATE UNIVERSITY IN MALAYSIA (Proceedings of the International Conference on Public Health, 2017)
Obesity is a major risk factor for various non-communicable diseases. The prevalence of obesity is on the rise, especially in younger populations. Improper eating patterns coupled with lack of physical activity have largely contributed to this problem. Medical students are exposed to social, cultural and study related stress during their course period. These factors influence their patterns of eating and physical activity. A cross sectional study was conducted among medical students of Taylors’ University to study their nutrition habits and exercise pattern. A total of 159 medical students participated in the study. It was found that 69.8% of students had normal BMI, 14.5% of students were underweight and 15.7% students were overweight or obese. It was observed that the prevalence of obesity was more in male students as compared to female students. Out of 159 students, 15.7% of students skipped breakfast. The major food items in the diet was a combination of rice, egg, meat and vegetables. It was also noted that 42.1 % of the students consumed soda drink at least once a week. Majority of our students were involved in intentional physical activity of some kind and they were aware about the importance of both good nutrition and physical activity in maintaining good health.
Keywords: obesity, medical students, exercise, nutrition